FTIR spectroscopy in biomedical analysis - Bunaciu, Andrei A. (Henry Stewart Talks, 2024)
Infrared (IR) spectroscopy, IR spectrum, IR spectroscopy in biomedical field, Biomedical diagnostic applications, Cancer analysis